2004
DOI: 10.1099/jmm.0.45721-0
|View full text |Cite
|
Sign up to set email alerts
|

Post-mortem culture of Balamuthia mandrillaris from the brain and cerebrospinal fluid of a case of granulomatous amoebic meningoencephalitis, using human brain microvascular endothelial cells

Abstract: The first isolation in the UK of Balamuthia mandrillaris amoebae from a fatal case of granulomatous amoebic meningoencephalitis is reported. Using primary cultures of human brain microvascular endothelial cells (HBMECs), amoebae were isolated from the brain and cerebrospinal fluid (CSF). The cultures showed a cytopathic effect at 20-28 days, but morphologically identifiable B. mandrillaris amoebae were seen in cleared plaques in subcultures at 45 days. The identification of the organism was later confirmed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 19 publications
0
49
0
2
Order By: Relevance
“…Likewise, the CSF samples from which ameba isolation had been attempted had been refrigerated or frozen for periods of hours to days, even before arrival at the laboratory (California Health Services). Although it is generally believed that Balamuthia is not found in CSF, Jayasekera et al (11) reported isolation of Balamuthia from CSF of a recent case in the United Kingdom.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the CSF samples from which ameba isolation had been attempted had been refrigerated or frozen for periods of hours to days, even before arrival at the laboratory (California Health Services). Although it is generally believed that Balamuthia is not found in CSF, Jayasekera et al (11) reported isolation of Balamuthia from CSF of a recent case in the United Kingdom.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, BAE has been reported in Asia, from Japan (two cases) (68), Thailand (one case) (30), and Australia (eight cases) (55); and in Europe, from the Czech Republic (one case) (37), Portugal (one case) (75), and the United Kingdom (one case) (83). An estimated 25 cases of BAE have been reported for previously healthy, immunocompetent individuals (5,20,24,27,30,32,34,40,44,57,83). The exact number of cases of BAE worldwide may never be known, which may be attributed to a lack of awareness, poor diagnosis, and poor public health systems, especially in less developed countries.…”
Section: Bae Epidemiology and Predisposing Factorsmentioning
confidence: 99%
“…The amoeba has been isolated from brain tissue (2,26,27) and, in a single case, from CSF obtained at autopsy (10). Neither the CSF nor unfixed brain tissue was available for attempting culture isolation of the amoeba.…”
Section: Case Reportmentioning
confidence: 99%